Mission indradhanush: A Sociological Study (International Journal of Food and Nutritional Sciences, 2022)
Immunization Programmes are one of the most well-recognized and successful public health programmes across the world. These programmes have achieved significant success in a number of countries; however, the coverage with available vaccines remains sub-optimal in many low and middle income countries (LMIC). The government has identified 201 high focus districts across the country under Mission Indradhanush. Nearly 50% of all unvaccinated or partially vaccinated children in India are in these 201 districts. Mission Indradhanush aims to strengthen key functional areas of immunization programme for ensuring high coverage throughout the country, with special attention to 201 identified high focus districts.